2358. Dementia and Cognitive Concerns are Risk Factors for Mortality in People with Human Immunodeficiency Virus and COVID-19. (15th December 2022) - Mukerji, Shibani S; Wilcox, Douglas R; Rudmann, Emily A; Ye, Elissa; Noori, Ayush; Magdamo, Colin; Alabsi, Haitham; Triant, Virginia A; Robbins, Gregory; Brandon Westover, M; Das, Sudeshna
Abstract: Background: Despite higher prevalence of cognitive disorders in people with human immunodeficiency virus (PWH) and dementia being a risk factor for COVID-19 mortality, the association between dementia and adverse outcomes in PWH with COVID-19 has not been well established. Methods: This was a matched case-control study (1:10) of patients with and without HIV at an academic institution with documented SARS-CoV-2 polymerase chain reaction (PCR) positivity from March 2020-March 2021. Data were extracted from the electronic health record data registry. PWH were matched to people without HIV (PWoH) by age, sex, race, and zip code. The primary exposures were dementia (identified using International Classification of Diseases, Tenth Revision codes) and cognitive concerns, defined as documentation of possible cognitive impairment up to 12 months prior to COVID-19 diagnosis and ascertained using a semi-automated natural language processing annotation tool. VACS 2.0 Index (including age, sex, body mass index, CD4+ T-cell count and HIV-1 RNA) was calculated. Logistic regression models assessed the effect of dementia and cognitive concerns on the odds of death (OR [95% confidence interval]), adjusted for VACS 2.0 Index. Results: Sixty-four (0.45%) PWH were identified among 14129 patients with COVID-19 and were matched to 463 PWoH. Among PWH, 59% were virally suppressed, and 14% had CD4< 200 cells/μL. Compared to 463 matched PWoH, PWH had higher prevalence of dementia (16% vs. 6%, p=0.01) and cognitive concerns (22% vs. 16%, p=0.04). Death was more frequent in PWH (17% vs. 6%, p< 0.01) and at younger ages (58 vs. 66 years, p=0.03). Cognitive concerns (2.5 [1.1–5.9], p=0.03) and dementia (3.4 [1.3–8.1], p=0.01) were significantly associated with increased adjusted odds of death in the overall group. Among PWH, cognitive concerns (7.2 [1.1–48], p=0.04) and dementia (6.0 [0.8–43.8], p=0.08) remained associated with mortality. Conclusion: Dementia and cognitive concerns were associated with mortality among PWH with COVID-19. The magnitude of the effect of cognitive impairment on COVID-19 outcomes may be greater in HIV, and additional studies with larger cohorts will help to assess this association further. Assessment of cognitive status is an important component to care for aging PWH in the COVID-19 era. Disclosures: All Authors : No reported disclosures.